KAJIAN TAMPUNGAN WADUK PEUDADA BERDASARKAN DEBIT BANJIR PERIODE ULANG T TAHUN TERHADAP PEMENUHAN KEBUTUHAN AIR MASYARAKAT DI KABUPATEN BIREUEN - Wesli, Wesli (Bumi Lestari; Vol 11 No 2 (2011), 2011)
Krueng Peudada River is located in sub district Peudada, Bireuen District, empties into the Strait of Malacca with a area watershed (catchment) of 425.8 km2. Water discharge is contributed by Krueng Wie River and Krueng Uneuen River. Subdistrict Peudada is an area prone to flooding, therefore the government made reservoir in the Meunasah Lawang village as an attempt to utilize the excess water as water source and as a flood control. Return period flood discharge plan is calculated by empirical formula method of Gumbel Type I. The result study shows the largest flood discharge at 50-year return period 333,282 m3/sec. To cope with likely flooding the reservoir Krueng Peudada planned dam height (H) 35 m and a summit elevation of +55 m and the area of 16,534,168 m2, so the total reservoir volume Peudada reservoir 329,419,094.58 m3. Volume used for water for all needs supply taken in an effective volume that is equal to 233,236,063.20 m3. The availability of water current (existing conditions) reached 0.971 m3/det, while the water needs for all the needs of 24.557 m3/det. In general, if there is a prolonged dry season, the water needs for all conditions can not be met. When the reservoir is at conditions effective volume, the reservoir is only capable of supplying water within 110 days
Keywords: water ballance, flood, reservoir